High day and night temperatures distinctively disrupt fatty acid and jasmonic acid metabolism, inducing male sterility in cotton. (8th August 2020) - Khan, Aamir Hamid; Min, Ling; Ma, Yizan; Wu, Yuanlong; Ding, Yuanhao; Li, Yanlong; Xie, Sai; Ullah, Abid; Shaban, Muhammad; Manghwar, Hakim; Shahid, Muhammad; Zhao, Yunlong; et al.
Abstract: High temperature stress is an inevitable environmental factor in certain geographical regions. To study the effect of day and night high temperature stress on male reproduction, the heat-sensitive cotton line H05 was subjected to high temperature stress. High day/normal night (HN) and normal day/high night (NH) temperature treatments were compared with normal day/normal night (NN) temperature as a control. At the anther dehiscence stage, significant differences were observed, with a reduction in flower size and filament length, and sterility in pollen, seen in NH more than in HN. A total of 36 806 differentially expressed genes were screened, which were mainly associated with fatty acid and jasmonic acid (JA) metabolic pathways. Fatty acid and JA contents were reduced more in NH than HN. Under NH, ACYL-COA OXIDASE 2 ( ACO2 ), a JA biosynthesis gene, was down-regulated. Interestingly, aco2 CRISPR-Cas9 mutants showed male sterility under the NN condition. The exogenous application of methyl jasmonate to early-stage buds of mutants rescued the sterile pollen and indehiscent anther phenotypes at the late stage. These data show that high temperature at night may affect fatty acid and JA metabolism in anthers by suppressing GhACO2 and generate male sterility more strongly than high day temperature. Abstract : Transcriptomic data analysis shows that disrupted fatty acid metabolism and jasmonic acid pathways contribute to male sterility in cotton in response to night high temperature stress by suppressing GhACO2 .